Möglichkeiten und Grenzen einer antizyklischen Geldpolitik - Ulrich Teichmann (Kredit und Kapital, 1972)
Possibilities and Limitations of Anticyclical Monetary Policy In our presentation we have set out (1) to enumerate the causes of the belated and therefore mostly procyclical effect of conventional monetary policy (in particular, drawing attention to the monetary recession amplifier), and (2) to develop from this point of departure cyclical strategies which help at least to limit those undesired effects, if not to eliminate them completely. We came to the following conclusion: When a state of marked overstimulation has already been reached because the impact of dynamic cyclical forces outweighs the effect of the – mostly belatedly applied – anticyclical measures, the possibilities of credit policy for subsequently offsetting that overstimulation without simultaneously laying the foundation for the next, similarly exaggerated countertrend are strictly limited. On the other hand, a monetary policy which is oriented not so much to cyclical extremes, but more to the intervening expansion and contraction phases, is more likely to succeed in stabilizing the overall economic trend. But since extensive strains on liquidity in the boom and expansion of liquidity in the recession impose a liquidity handicap on anticyclical policy in the responsive intermediate phases, any monetary strategy must accordingly not be directed against current exaggerated trends for the short run only, but must make allowances in the measures adopted also for the impact on the following phases and include it in the cyclical policy calculus. For instance, it may be expedient to desist from present intensive employment of monetary instruments in favour of a later phase in which they can be used more appropriately, and to perform the current task with other means, as a rule the means of fiscal policy.
Keywords: 330